Investigating key factors for female players to generate comparable interaction torque to that of male players - Iitake, T.; Nunome, H. (ISBS Proceedings Archive (Michigan), 2023)
We aimed to clarify the kinetic strategy of female players to achieve comparable motion-dependent interaction torque to that of male players during soccer instep kicking. The kicking leg motion of female and male players was captured at 500 Hz. The interaction torque was decomposed into two components due to the kicking leg and the support leg actions using the procedure of Inoue et al., (2013). Female players exhibited significantly smaller counter-clockwise (positive) interaction torque due to the support leg action while the clockwise (negative) component due to the kicking leg action was significantly suppressed in the latter part of kicking than male players. Our findings suggest coaches and female players should pay more attention to the kicking leg posture during the latter part of the leg swing to maintain their effective action of the interaction torque.